1979
DOI: 10.1111/j.1751-1097.1979.tb07204.x
|View full text |Cite
|
Sign up to set email alerts
|

Branching in the Bacteriorhodopsin Photochemical Cycle

Abstract: Kinetics have been determined for the decay of the terminal phototransients M(410) and O(660) and the reappearance of the BR(570) chromophore in flash-photolyzed aqueous suspensions of light-adapted purple membrane fragments from Halobacterium halobium. The results were fitted to a linear model of A k2 M(410)-O(660) -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 15 publications
(7 reference statements)
5
14
0
Order By: Relevance
“…The effect of temperature on the photocycle has been studied by several investigators (20)(21)(22). Racker and Hinkle (23) studies showed that increasing temperature decreased the efficiency of proton uptake by reconstituted phospholipid vesicles containing bR, a result qualitatively similar to that reported here.…”
Section: Discussionsupporting
confidence: 78%
“…The effect of temperature on the photocycle has been studied by several investigators (20)(21)(22). Racker and Hinkle (23) studies showed that increasing temperature decreased the efficiency of proton uptake by reconstituted phospholipid vesicles containing bR, a result qualitatively similar to that reported here.…”
Section: Discussionsupporting
confidence: 78%
“…At 45°C the maximum concentration of 0 -B R is more than 3 times higher than at 14°C (Gillbro, 1978). The reason for this temperature effect is probably that the rate of 0 -B R formation is much slower than its decay rate at lower temperatures (Gillbro, 1978) or alternatively that there is a temperature-sensitive branching of the photocycle between M-BR and 0 -B R (Sherman et a/., 1979). We did not notice any change in the ps signal of Figure 1 as the temperature of the sample was varied between 0 and 30°C.…”
Section: Identification Of the Photoproductmentioning
confidence: 75%
“…1 a). This assumption is based on the observation that the ratio between apparent time constants of formation and decay of the O0 intermediate is practically temperature independent (7); hence, the temperature dependence of the O0 maximum reflects the dependence of the transient concentration of the O0 intermediate, which is illustrated in the transmittance record of Fig. 1 tional T-jump pulses at two diffc photocycle.…”
Section: Resultsmentioning
confidence: 99%